Temporal aspects of the visuotactile congruency effect. - Shore, D; Barnes, M; Spence, C (2006)
We report an experiment designed to investigate the temporal dynamics of the visuotactile crossmodal congruency effect. Vibrotactile targets were presented randomly to the index finger (top side of a hand-held cube) or thumb (bottom side) of either hand while visual distractors were presented randomly from one of the same four possible locations. The stimulus onset asynchrony (SOA) between the vibrotactile target and the visual distractor was varied on a trial-by-trial basis. Participants made speeded discrimination responses regarding the elevation of the vibrotactile targets (i.e., upper versus lower) while trying to ignore the visual distractors. The largest crossmodal congruency effects (defined as the difference in performance between incongruent and congruent elevation distractor trials) were obtained when the visual distractor preceded the vibrotactile target by 50-100 ms, although significant effects were also reported when the distractor followed the target by as much as 100 ms. These results are discussed in terms of the conjoint influence of response competition, crossmodal perceptual interactions (i.e., the ventriloquism effect), and exogenous spatial attention on the crossmodal congruency effect. The distinct temporal signatures of each of these effects are also highlighted.